Innovativeness and Competitiveness of the Western Balkan Countries and Selected EU Member States - Despotovic, Danijela Zoran; Cvetanović, Slobodan Ž; Nedić, Vladimir M (Industrija, 2014)
Given that innovativeness stands for one of the most significant categories in the process of investigating key economic phenomena, including competitiveness of economy, the paper will: a) explain the metrics of The Global Innovation Index and The Global Competitiveness Index, as two undoubtedly most significant analytical frameworks for expressing the achieved level and key determinants of innovativeness, on the one hand, and the factors of countries’ competitiveness at the global level, on the other hand, and b) provide empirical analysis of the correlation between innovativeness and competitiveness of the Western Balkan countries (Albania, Bosnia and Herzegovina, Macedonia, Serbia, Croatia, and Montenegro), the European Union member states from the region (Austria, Bulgaria, Greece, Hungary, Romania and Slovenia). After applying the adequate methodology, a conclusion was made that: a) Western Balkan countries lag behind the European Union member states in the level of innovativeness, and b) from the aspect of correlation between innovativeness and countries’ competitiveness, statistically significant correlation has not been determined for the Western Balkan countries, unlike selected EU member states where a strong linear correlation between these variables has been determined in 2012.